Identification and screening of chemical constituents with hepatoprotective effects from three traditional Chinese medicines for treating jaundice. Issue 19 (October 2016) - Wang, Shufang; Li, Xiaodong; Niu, Yan; Liu, Yining; Zhu, Yunxiang; Lu, Xiaoyan; Fan, Xiaohui; Zhang, Xingxian; Wang, Yi
Abstract : The constituents with hepatoprotective activity were investigated in three traditional Chinese medicine formulae for treating jaundice, namely, Zhi‐Zi‐Da‐Huang‐Tang, Yin‐Chen‐Hao‐Tang, and Da‐Huang‐Xiao‐Shi‐Tang. By using liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry and liquid chromatography coupled with ion trap mass spectrometry, 79 chemical constituents were identified unambiguously or tentatively in three formulae based on the accurate molecular weight, mass spectrometric fragmentation behavior, and comparison with reference standards. Then the hepatoprotective activities of 27 constituents were evaluated on tert ‐butylhydroperoxide‐injured BRL‐3A cells. The results indicated that 11 constituents, including protocatechic acid (19 ), epijasminoside A (56 ), rutin (71 ), tetrahydropalmatine (76 ), rhaponticin (80 ), 3, 4‐dicaffeoylquinic acid (82 ), 3, 5‐dicaffeoylquinic acid (85 ), diosmetin‐7‐ O ‐glucoside (90 ), jatrorrhizine (93 ), berberine (100 ), and daidzein (101 ) exerted hepatoprotective activities. Interestingly, most of the crude drugs in three formulae contained hepatoprotective active constituents, and the combinations of constituents from different crude drugs exhibited greater effects. This result provided evidence to the traditional Chinese medicine theory of combining several drugs together to exert synergistic efficacy.